ABOUT ACCOUNT OF STRUCTURAL NOISE IN CABINS OF CRANES - S.A. RAZDORSKIJ (Вестник Донского государственного технического университета, 2018)
In operation influence of vibration of elements of a protection of a cabin of the bridge crane on formation of structural noise is considered. Having applied a method of an energy balance expressions of a vibration speed are obtained depending on an entered vibration power of external sources. Possible ways of drop of levels of a sound pressure on workplaces of crane operators are considered.